2021
DOI: 10.1101/2021.03.10.434352
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A redox-dependent mechanism for AMPK dysregulation interrupts metabolic adaptation of cancer under glucose deprivation

Abstract: Accelerated aerobic glycolysis is a distinctive metabolic property of cancer cells that confers dependency on glucose for survival. However, the selective therapeutic targeting of this vulnerability has yielded mixed results owing to the different sensitivities of each cancer type to glucose removal and lack of insight into the underlying mechanisms of glucose deprivation-induced cell death. Here, we screened multiple cell lines to determine their sensitivities to glucose deprivation and found that the cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…We speculate that prolonged cell stress upon dual PFKFB3 and EGFR inhibition leads to deregulated AMPK function which, in turn, might contribute to the impaired autophagy flux observed in the combo-treated cells. Recently, it has been shown that prolonged glucose deprivation results in AMPK deregulation that interrupts metabolic adaptation and causes rapid cell death [ 63 ]. Moreover, recent studies have shown that in LKB1-mutant cells, glucose starvation elicits an oxidative stress, which causes AMPK protein oxidation and inactivation, and eventually cell death [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that prolonged cell stress upon dual PFKFB3 and EGFR inhibition leads to deregulated AMPK function which, in turn, might contribute to the impaired autophagy flux observed in the combo-treated cells. Recently, it has been shown that prolonged glucose deprivation results in AMPK deregulation that interrupts metabolic adaptation and causes rapid cell death [ 63 ]. Moreover, recent studies have shown that in LKB1-mutant cells, glucose starvation elicits an oxidative stress, which causes AMPK protein oxidation and inactivation, and eventually cell death [ 64 ].…”
Section: Discussionmentioning
confidence: 99%